The effect of activities of daily living on anxiety in older adult people: the mediating role of social participation - Zheng, Juan; Xu, Jianqiang; Liu, Daqi (Frontiers in Public Health, 2024)
ObjectiveAnxiety is a serious psychiatric illness in older adult people. Activities of daily living and social participation are important factors influencing anxiety in older adult people. Using social participation as a mediating variable, this study explored the influence of activities of daily living on anxiety in older adult people to provide scientific evidence for improving the psychological health of older adult people.MethodsA multistage stratified random sampling method was used in this study to recruit older adult people. T tests and variance analysis were used for single factor analysis, and a multiple linear regression model was used for multifactor analysis. Pearson correlation analysis was used to study the correlation between activities of daily living and social participation and anxiety. The Process program was used to perform the bootstrap test.ResultsThe mean anxiety score of the interviewed older adult individuals was 3.028 ± 4.606 points, and 28.66% of the older adult individuals had anxiety. There was a statistically significant difference in the anxiety scores of older adult people across sex, age, marital status, education level, and health insurance status (p < 0.05). After controlling for other variables, each one-point increase in the activities of daily living score significantly increased the anxiety score by 0.122 points (𝛽=0.122, p < 0.001), and each one-point increase in the social participation score significantly decreased the anxiety score by 0.058 points (𝛽= − 0.058, p < 0.001). According to the results of the mediating effect analysis, there was a significant positive relationship between activities of daily living and anxiety, and the total effect was established (𝛽=0.1719, p < 0.001). After controlling for social participation, there was a significant direct effect of activities of daily living on anxiety in older adult people (𝛽=0.1255, p < 0.001). A partial mediating effect of social participation on the relationship between activities of daily living and anxiety in older adult people was found. The indirect effect of social participation was 26.99%.ConclusionActivities of daily living and social participation are important factors affecting anxiety in older adult people. Health education should be increased to enhance the physical activity of older adult people to improve their activities of daily living, create a good atmosphere for their social participation, improve their motivation for and continuity of social participation.